Community search from multi-attributed large social graph - Khan, Riasat Islam; Khan, Sayed Mahmud; Debnath, Tanmoy; Islam, Md. Nazmul; Kayes, Muhtasim Ibne (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.